Bắt nạt học đường và lòng tự trọng ở học sinh trung học phổ thông: Khảo sát tại thành phố Hải Phòng - Phạm Ngọc Linh; Nguyễn Hồng Đào, Nguyễn Hồng Đào (Tạp chí Giáo dục, 2026)
School bullying is one of the psychological and social issues of concern in the current educational environment. This study aims to examine the prevalence of school bullying and analyze the correlation between school bullying and self-esteem among high school students. The research was conducted with 206 students in Hai Phong City using a questionnaire survey method. The research instruments included the School Bullying Scale for Vietnamese Children and the Rosenberg Self-Esteem Scale. The results indicate that 10.7% of students reported experiencing bullying within one year prior to the time of the survey. Pearson correlation analysis revealed a statistically significant negative correlation between school bullying and students’ self-esteem (r = −0.243; p < 0.01). These findings suggest that preventing and reducing school bullying not only helps improve students’ self-esteem but also contributes to building a healthy and safe school environment — both physically and psychologically. This provides a scientific foundation for schools and school counselors to develop appropriate intervention programs, ranging from individual counseling to workshops and group or community-based projects.